Decoding the tasks of sociology. A situational state of the labor market for sociologists in Peru - Evans Morales, Franco (2022)
The article has two objectives. To examine the employability characteristics of sociologists in the Peruvian labor market, and 2. To analyze the elements that make sociology a profession with capacity for recognition and public value in the system of professions. The methodology follows a mixed approach: for the first objective, 225 surveys were applied to sociologists from the Peruvian Association of Sociologists at the national level; for the second objective, eight interviews were conducted with sociologists who studied sociology at different universities in Peru. The results of the surveys show that employability is positioned in the public sector and the three levels of national government concentrate the highest percentages of job placement, to which is added the self-assessment of the social specialist as a generic typology of labor practice. The qualitative findings reveal that sociology can be recognized by the first level of attention to people’s demands, the distinction of theory-methodology, as well as the valuation of social processes and the critique of operational routinization within employment.